Optimization of Pediatric Surgery Services: An Integrated Approach - Trismayanti, Ni Made Rika; Gunadi, Gunadi; Meliala, Andreasta (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
The background of this journal explores the urgency of improving pediatric surgery services through infrastructure development, increasing the competence of medical personnel, and implementing better service standards with the end result of increased visits and patient satisfaction. In addition, this study also highlights the challenges faced and effective strategies to overcome obstacles in efforts to optimize pediatric surgery services at Persahabatan Hospital (RSP). This study aims to explain the factors related to the optimization of pediatric surgery services at RSP and formulate the concept of optimizing pediatric surgery services at RSP. This study uses a qualitative research design with descriptive analysis. This study was carried out by observation and filling out questionnaires by the families of pediatric surgery patients and hospital management related to pediatric surgery services at RSP, with a SWOT analysis. The average strength rating is 4.49; The average weakness rating is 3.55; The average opportunity rating is 4.07; The average threat rating is 3.49. The most appropriate strategy for RSUPP is the SO strategy or aggressive strategy (0.475; 0.299). The Strengths Opportunities method is most suitable for optimizing pediatric surgery services at RSP, namely the use of strategic locations, medical personnel, and complete infrastructure. Research on pediatric surgery services has never been done in Indonesia. Unfortunately, this research was only carried out at RSP, and could not be applied nationally.